Global statements to produce and implement evidence in the post-COVID-era provide a path forward for rehabilitation - A joint initiative of Cochrane Rehabilitation and the leading journals in the field - Stefano Negrini; Kristian Borg; Anne Cusick; Giorgio Ferriero; Walter R Frontera; Douglas P Gross; Allen Heinemann; Wendy Machalicek; Ann Patricia Moore; Randolph J Nudo; Dominic Pérennou; Henk Stam; et al. (Medical Journals Sweden, 2022)
This paper is supported and co-published by the following journals, and their Editors in Chief: Annals of Physical and Rehabilitation Medicine − Dominic Pérennou American Journal of Physical Medicine & Rehabilitation − Walter Frontera Developmental Neurorehabilitation − Wendy Machalicek European Journal of Physical and Rehabilitation Medicine − Stefano Negrini and Giorgio Ferriero Journal of Occupational Rehabilitation − Douglas Gross Journal of Rehabilitation Medicine − Kristian Borg and Henk Stam Musculoskeletal Science & Practice − Ann Moore Neurorehabilitation and Neural Repair − Randolph Nudo